Análisis del nivel de acceso a crédito para el emprendimiento de la juventud lojana y propuesta de un programa educativo para su fortalecimiento - Zapata Ramírez, Daniel Eduardo (2022)
Access to credit for entrepreneurship often represents a problem, since applicants are unable to meet the requirements requested by financial institutions. This degree work was developed with the objective of knowing the level of access to credit that young people with an age range of 18 to 29 years in the city of Loja have, for this 382 surveys were applied to collect relevant information on the population behavior in the area and what are the main constraints to access financing. Once the information was collected, statistical and mathematical tools were used to process the information, obtaining that 75% of young people in the city of Loja do not have access to financing through financial institutions. This is due to high interest rates, excessive documentation or guarantees, which discourage the population because they do not meet the expectations sought by young people. Finally, it is established that in the city of Loja there is little support from traditional banks for youth entrepreneurship and innovation, since their lines of credit are focused on consumption and concentrate on people with greater purchasing power. Therefore, a new educational program and credit product focused on the national public financial system is proposed to be offered in order to encourage entrepreneurship and economic dynamization in the city of Loja.